The effect of age and gender on labor demand - evidence from a field experiment - Magnus Carlsson; Stefan Eriksson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
In most countries, there are systematic age and gender differences in labor market outcomes. Older workers and women often have lower employment rates, and the duration of unemployment increases with age. These patterns may reflect age and gender differences in either labor demand (i.e. discrimination) or labor supply. In this study, we investigate the importance of demand effects by analyzing whether employers use information about a job applicant's age and gender in their hiring decisions. To do this, we conducted a field experiment, where over 6,000 fictitious resumes with randomly assigned information about age (in the interval 35-70) and gender were sent to employers with a vacancy and the employers' responses (callbacks) were recorded. We find that the callback rate starts to fall substantially early in the age interval we consider. This decline is steeper for women than for men. These results indicate that age discrimination is a widespread phenomenon affecting workers already in their early 40s in many occupations. Ageism and occupational skill loss due to aging are unlikely explanations of these effects. Instead, our employer survey suggests that employer stereotypes about three worker characteristics - ability to learn new tasks, flexibility/adaptability, and ambition - are important. We find no evidence of gender discrimination against women on average, but the gender effect is heterogeneous across occupations and firms. Women have a higher callback rate in female-dominated occupations and firms, and when the recruiter is a woman. These results suggest that an in-group bias affects hiring patterns, which may reinforce the existing gender segregation in the labor market.
Keywords: J23; J71; 330; Age; gender; discrimination; field experiment; labor market